Strengthening Arabic Language Learning through Total Quality Management (TQM) - Miftahul Huda; Wasilah Wasilah; Jamanuddin Jamanuddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The background of this study is the various challenges in Arabic language learning at MTs Ma'ariful Ulum Banyuasin, such as low teaching effectiveness, limited facilities, and minimal use of digital technology in the teaching and learning process. These problems require a managerial and pedagogical approach that can improve the quality of learning in a sustainable manner. This study aims to describe the implementation of Total Quality Management (TQM) in Arabic language learning at the madrasah. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews with teachers and the head of the madrasah, as well as documentation of teaching tools and learning journals. The results of the study show that TQM principles have been thoroughly internalized in three main aspects of learning, namely planning, implementation, and evaluation. At the planning stage, teachers and madrasah principals conduct collaborative evaluations and analyze student needs to develop relevant teaching tools. In practice, teachers implement active, communicative, and contextual learning, and adapt methods and media to students' learning styles. Formative and summative evaluations are conducted using authentic instruments, portfolios, and learning journals as a basis for decision making. In addition, reflective practices through internal MGMPs, student learning satisfaction surveys, and appreciation for teacher innovation demonstrate the continuous strengthening of a culture of quality. Despite constraints such as limited facilities and digitization, the implementation of TQM has proven to improve the effectiveness and sustainability of Arabic language learning. These findings confirm that TQM can be effectively applied not only at the managerial level but also directly in the classroom.